Analisis Faktor Risiko Distres pada Petugas KPPS di Tangerang Selatan: Studi Kasus Pemilu Tahun 2024 - Sari, Puti Intan; Erwandi, Dadan (UI Scholars Hub, 2025)
General elections or elections are processes for citizens to elect the president, vice president, and representatives directly. Elections are organized by various organizations or bodies, one of which is the polling station organizing group (KPPS). Based on studies, KPPS officers bear a heavy workload leading to distress among them. This research aims to analyze distress risk factors among KPPS officers in South Tangerang during the 2024 elections. The study uses a quantitative method with a cross-sectional study design. Data analysis involves descriptive and inferential statistics. The results show that 68.8% of the officers experience moderate stress, while 31.2% experience mild stress. Furthermore, there is a significant correlation between physical work environment, workload, age, and gender with the level of distress. Keywords: distress, KPPS officers 2024 elections, job factors, individual factors, supporting factors.